Navigating green hospitality: Gen Z’s role in shaping sustainable hotel practices through conjoint analysis - Deshani, Swati Haridas; Rana, Vikash; Agrawat, Preeti (International Journal of Management and Sustainability, 2025)
Generation Z (Gen Z) is driving the new age of hospitality, characterized by its environmental consciousness and technological adeptness. The hotel industry must adapt to align with the values and demands of these environmentally aware individuals. However, the need for frameworks to translate Gen Z’s environmental objectives into operational strategies is critical. This study utilizes conjoint analysis to identify and prioritize sustainability dimensions that influence Gen Z’s hotel preferences. It highlights five determinants: Awareness of Practices (25%), Sustainable Sourcing (22%), Energy Efficiency (20%), Waste Management (18%), and Community Engagement (15%). Transparency in sustainability practices, including certifications and demonstrable actions, emerges as the most significant factor for Gen Z. Ethical sourcing and supporting local products also hold great importance. Greener practices, waste management, and community engagement are key to building trust with this generation. The findings address a gap in the literature regarding Gen Z’s eco-sustainability orientation through data-driven insights. The study suggests actionable measures for hotels, governments, and stakeholders, emphasizing transparency, ethical sourcing, and community involvement to attract Gen Z customers. These strategies not only enhance competitiveness but also contribute to global sustainability goals. Academically, the research advances the application of conjoint analysis in the hotel industry, paving the way for future studies. The implications extend beyond academia, urging the hospitality sector to integrate green practices that foster a balanced environment and stronger communities.